Strategi Pengendalian Alih Fungsi Lahan Pertanian di Subak Kerdung, Kelurahan Pedungan, Kecamatan Denpasar Selatan, Kota Denpasar - IKHSAN, LATIEF; WINDIA, I WAYAN; ASTITI, NI WAYAN SRI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.8, No.2, April 2019, 2019)
Strategy for Controlling the Transfer of Agricultural Land Functions in SubakKerdung, Sub-District of South Denpasar, Denpasar City Control over the conversion of agricultural land is very necessary in order to maintain the existence and sustainability of subak in the City of Denpasar, especially in SubakKerdung. There needs to be appropriate strategies as a solution so that control over the conversion of agricultural land in SubakKerdung can be done. The purpose of this study was to determine internal and external factors and to find out the most appropriate strategy in controlling the conversion of agricultural land in SubakKerdung. The results of the analysis of internal factors in SubakKerdung were: a) strength (the application of Tri Hita Karana in subak), b) weakness (low interest of subak members to defend their land). External factors were: a) opportunities (the development of ecotourism as a tourist attraction), b) threats (over the function of agricultural land).Based on the SWOT analysis, the development strategies found were: (a) S-O Strategy - Optimizing the empowerment of farmer communities as the main actors in ecotourism development by directly selling their agricultural products to tourists. (b) WO Strategy - Conducting education and training through counseling in adopting new innovations so that agricultural products can be marketed to tourists. (c) S-T Strategy - Planting vegetables that have high economic value and can be processed into snacks and drinks (d) The W-T Strategy -Implementing and increasing the intensity of education and training on tour guides, i.e. English training for young people and farming communities.